A Retrospective Study Analyzing the Lack of Symptom Benefit With Antimicrobials at the End of Life. (April 2021) - Lopez, Santiago; Vyas, Pooja; Malhotra, Prashant; Finuf, Kayla; Magalee, Christopher; Nouryan, Christian; Hirsch, Bruce
Background: Infections are common in terminally ill patients (pts), and although antibiotics are frequently prescribed, their benefit for symptom relief is not clear. Antimicrobials at the end of life (EOL) may increase the risk of antimicrobial resistance and Clostrioides difficile infection. Our aim was to determine the frequency of symptom occurrence at the EOL when comparing pts who did or did not receive antibiotics (AB+ or AB-). Methods: We reviewed electronic medical records of pts admitted to a palliative care unit of a quarternary care hospital between 01/09/2017 and 07/16/2017 and assessed antimicrobial use in the last 14 days of life. Differences in demographics and symptom control between AB+ and AB- pts were analyzed using chi-square analyses; p-values were computed using Mann-Whitney tests. Results: Of a total of 133 pts included, 90 (68%) received antimicrobials (AB+). The indication for antibiotics was documented in only 12% of pts. The AB+ and AB- groups were similar with respect to demographics, including sex, and Charleston Comorbidity Index except for age (p = 0.01) and race (p = 0.03). Documented infections were similar between AB+ and AB- groups, except urinary tract infections. No statistically significant differences were noted in documented symptoms including pain, dyspnea, fever, lethargy, and alteration of mental state or length of stay. Conclusion: Our study did not show differences in frequencies of documented symptoms with use of antimicrobials at EOL. Antimicrobial stewardship programs and further research can help with developing EOL care antimicrobial guidelines supporting patients and providers through shared decision-making.